Functional genomics study of acute heat stress response in the small yellow follicles of layer-type chickens - Cheng, Chuen-Yu; Tu, Wei-Lin; Chen, Chao-Jung; Chan, Hong-Lin; Chen, Chih-Feng; Chen, Hsin-Hsin; Tang, Pin-Chi; Lee, Yen-Pai; Chen, Shuen-Ei; Huang, San-Yuan (Scientific reports, 2018)
This study investigated global gene and protein expression in the small yellow follicle (SYF; 6–8 mm in diameter) tissues of chickens in response to acute heat stress. Twelve 30-week-old layer-type hens were divided into four groups: control hens were maintained at 25 °C while treatment hens were subjected to acute heat stress at 36 °C for 4 h without recovery, with 2-h recovery, and with 6-h recovery. SYFs were collected at each time point for mRNA and protein analyses. A total of 176 genes and 93 distinct proteins with differential expressions were identified, mainly associated with the molecular functions of catalytic activity and binding. The upregulated expression of heat shock proteins and peroxiredoxin family after acute heat stress is suggestive of responsive machineries to protect cells from apoptosis and oxidative insults. In conclusion, both the transcripts and proteins associated with apoptosis, stress response, and antioxidative defense were upregulated in the SYFs of layer-type hens to alleviate the detrimental effects by acute heat stress. However, the genomic regulations of specific cell type in response to acute heat stress of SYFs require further investigation.